Genetic testing of sperm donors at a human sperm bank in China - Huang, Chuan; Wu, Hui-Lan; Zhou, Wen-Jun; Huang, Zeng-Hui; Luo, Xue-Feng; Tang, Yu-Ling; Liu, Qian; Fan, Li-Qing; Nie, Hong-Chuan; Zhu, Wen-Bing (Frontiers in Endocrinology, 2022)
Background: In China, numerous human sperm banks only perform three-generation family history analysis to exclude genetic diseases with clinical symptoms; therefore, many inherited risks cannot be detected before donor qualification even when a thorough genetic family history evaluation has been performed. Hence, the risk of recessive disease inheritance persists with the current eligibility guidelines in China regarding the donor selection process. Methods: Retrospective study that reviewed the genetic test analyses and clinical outcomes of young adult men who were qualified sperm donors at the Hunan Province Human Sperm Bank of China from January 1, 2018, to May 1, 2021. We included a total of 3231 qualified sperm donors: all donors underwent primary screening for thalassemia and glucose-6-phosphate dehydrogenase (G6PD) deficiency. Whereafter, 278 of donors underwent genetic testing for specific genes, and 43 donors underwent whole exome sequencing. Results: 2.4% of 3231 qualified sperm donors might have thalassemia and 1.4% might have G6PD deficiency. Sperm donors with thalassemia and G6PD deficiency would be eliminated. Specific gene testing identified 7 of the 278 donors (2.5%) as carriers of at least one pathogenic or likely pathogenic variant in a gene, including 1.9% of 154 donors (3/154) as carrier variants in α-Like or β-Like globin genes, 17.6% of 17 donors (3/17) as carrier variants in GJB2, 12.5% of 8 donors (1/8) as carrier variants in SMN1. In addition, among the 43 sperm donors carrying the 111 pathogenic/likely pathogenic variants, eight (18.6%) were carriers of pathogenic variants of the GJB2 gene. The frequency, therefore, was approximately 1 in 5. Conclusions: The data suggest that used blood routine and RDT can make a preliminary screening of sperm donors, and special gene testing should be performed for sperm donors according to the regional incidence of specific genetic diseases. Meanwhile, whole exome sequencing can be used as a supplementary application in sperm donor genetic testing, and aid a successful and healthy pregnancy. However, industry guidelines must be modified to incorporate its use.